Developmental toxicity of endocrine-disrupting chemicals: Challenges and future directions - Pizent, Alica (Archives of Pharmacy, 2021)
Maternal exposure to a mixture of various endocrine disruptors (EDCs) may have a substantial impact on postnatal health of her offspring(s) and increase the risk for health disorders and diseases in adulthood. Research efforts to better understand the health risk associated with endocrine disruptor exposures in early life have increased in recent decades. This paper provides a short overview of the current challenges that researchers continue to face in selecting appropriate epidemiologic methods and study designs to identify endocrine disruptors and evaluate their adverse health effects during this critical developmental window. Major challenges involve the selection of a representative biomarker that reflects the foetal internal dose of the biologically active chemical or its metabolite(s) that may be associated with adverse health effects with regard to variable level and duration of exposure and the latency between exposure and disorder/disease manifestation. Future studies should pay more attention to identifying factors that contribute to interindividual variability in susceptibility to various EDCs and other toxicants.
Keywords: Endocrine-disrupting chemicals; developmental origins of health and disease; epidemiologic research; biomonitoring; biomarkers